Longitudinal Opioid Surveillance Project Involving Toxicologic Analysis of Postmortem Specimens from 9 Counties in Michigan Suggests the Discovery of New High-Intensity Drug Trafficking Areas. (4th September 2021) - Stevens, Christine; Li, Tong; Ton, Erinn; Zou, Jalynn; Douglas, Elizabeth; Jones, Prentiss
Abstract: Acetyl fentanyl (AF) is a Schedule I fentanyl analog that has been increasingly seen in heroin and fentanyl polydrug toxicity overdoses in Michigan (MI). Drug users are often unaware of the presence of AF in their drugs because it is often sold mixed into or disguised as heroin. High levels of AF in heroin drug products can cause increased incidence of overdose. This article describes data from a longitudinal opioid surveillance program and details 102 decedents in MI who were found to have evidence of heroin in their postmortem blood. A large portion of these decedents were also found to have evidence of fentanyl and AF. Our data further show significant overlap in incidence rates of AF and heroin-related overdose deaths in several MI counties, suggesting that AF is becoming enmeshed in heroin trafficking. Furthermore, we report unprecedented high incidence rates of AF and heroin-related overdose deaths in Calhoun county, and we propose that it is a high-intensity drug trafficking area. Highways US-131 and US-31 are likely used to transport these drugs. More study is needed into the drug trafficking trends in MI to ascertain drug sources and monitor the ever developing and dangerous polydrug heroin combinations.